Probabilistic approach to the reliability of steel bridge structures - Slavík, Jiří; Vičan, Josef; Šertler, Hynek (Univerzita Pardubice, 1996)
The paper describes a probability-based concept for the evaluation of existing bridges. Firstly the standard concept of the Live Load Rating Factor (LLRF) calculation is presented. Secondly, the probability-based concept of the Traffic Load Rating Factor (TLRF) calculation is described. The determination of TLRF is introduced in two approaches. Both approaches enable to respect the main reliability differences between evaluation of existing bridges and design of the new ones affecting the failure probability level. Numerical applications are presented to demonstrate described approaches.
Pravděpodobnostní výpočet spolehlivosti ocelových mostních konstrukcí
Probabilische Berechnungsweise der Zuverlässigkeit der Brückenstahl Konstructionen